The Integration of Macroscopic Tumor Invasion of Adjacent Organs into TNM Staging System for Colorectal Cancer - Liang, Ji-wang (Public Library of Science, 2012)
OBJECTIVE: In addition to pathological TNM (pTNM) staging, the macroscopic staging (surgical TNM, sTNM) is another method used to stage and assess tumors, and it also potentially influences patient treatment guidelines. However, for the same patient, surgeons and pathologists might assess tumor depth differently. We aimed to evaluate the prognosis of patients who exhibit unconformity of intraoperative and postoperative results and propose a revised pT category (r-pT category) to predict survival in colorectal cancer. METHODS AND RESULTS: In our study, 948 colorectal cancer patients were reviewed. We proposed a novel r-pT category in which surgical macroscopic T4b (sT4b) is incorporated into the pT category, namely, patients in the pT3 category with sT4b cancers are reclassified as being in the r-pT4a category; patients in the pT4a category with sT4b cancers are reclassified as being in the r-pT4b category. Cancer-specific survival according to the r-pT category was analyzed using Kaplan-Meier survival curves. A two-step multivariate analysis was used to determine correlations between the r-pT category and the prognosis. Harrell’s C statistic was utilized to test the predictive capacity. There were significant prognostic differences among the r-pT subcategories. We substituted the r-pT category for the pT category in current TNM staging in a 2-step multivariate analysis. The Harrell’s C statistical analysis results demonstrated that the r-pT category had superior predictive capacity compared to the pT category (Harrell’ C: 0.668 vs. 0.636; P = 0.002). CONCLUSIONS: Patients in the pT3 category with sT4b cancers, and patients in the pT4a category with sT4b cancers, are potentially under-staged, reclassification into higher categories could potentially benefit these patients. The results indicate that the r-pT category we proposed is potentially superior to the pT category in the assessment of prognosis for colorectal cancer.